Taking Erap jokes seriously a case study of Erap jokes and its appropriation as a political communication tool used in Joseph Estrada's campaign for the presidency - dela Cruz, Dianne Jeanne B. 1980-
This study analyzes how Erap jokes helped Joseph Estrada win the 1998 presidential elections. It tries to ascertain whether the conception, dissemination, and propagation of Erap jokes were deliberately used as a campaign tool and to discern how the image of Estrada was created and reinforced by the jokes. Lastly, this study also analyzed how humor effected positive attitude change among voters. The researchers interviewed experts in the fields of public relations, anthropology, political analysis, sociology, and joke writing. This study found that Erap jokes worked positively for Estrada and generated awareness, name recall and empathy among voters. The use of Erap jokes were deliberate in Estrada's campaign for the presidency. His public relations team recognized the potential of the jokes as a campaign tool, and turned it into Estrada's asset. The jokes gave Estrada enormous positive exposure, since the nature of the jokes lent itself to being constantly retold through word of mouth. The jokes were Estrada's ticket to the consciousness of the elite, and were also the reinforcement of his populist image among the masses.